The Nitrogen Isotopic Composition of Tissue and Shell‐Bound Organic Matter of Planktic Foraminifera in Southern Ocean Surface Waters. (18th February 2020) - Smart, Sandi M.; Fawcett, Sarah E.; Ren, Haojia; Schiebel, Ralf; Tompkins, Emily M.; Martínez‐García, Alfredo; Stirnimann, Luca; Roychoudhury, Alakendra; Haug, Gerald H.; Sigman, Daniel M.
Abstract: We present the first nitrogen isotope (δ 15 N) measurements of planktic foraminifera, paleoceanographically important zooplankton, from the nutrient‐rich waters of the modern Southern Ocean. Foraminifera were collected from net tows in the Subantarctic and Polar Frontal Zones (SAZ and PFZ, respectively) south of Africa during winter 2015 and late summer 2016. In late summer, consistent with preferential uptake of 14 N‐nitrate and the progressive, northward depletion of nitrate by phytoplankton across the Southern Ocean, foraminifer tissue and shell‐bound δ 15 N rise equatorward along with nitrate δ 15 N. However, foraminifer δ 15 N is ~3‰ lower than expected for heterotrophs relying on photosynthetic biomass generated directly from nitrate. This discrepancy appears to originate with the particulate organic N (PON) in late‐summer surface waters, the δ 15 N of which is lowered by ammonium recycling. In winter, when overall productivity and foraminifer production are reduced, foraminifer δ 15 N is higher (by 4.6 ± 0.8‰ for tissue and by 4.0 ± 1.5‰ for shell‐bound N compared to late summer) and exhibits no clear north‐south trend. These characteristics can also be explained by the feeding‐driven connection of foraminifera to PON, which is elevated in δ 15 N by net degradation in winter. Therefore, foraminifer δ 15 N is more closely tied to PON δ 15 N than to nitrate δ 15 N in the Southern Ocean mixed layer. Combining our isotope data with previously reported sediment trap fluxes from the western Pacific SAZ/PFZ suggests that, under modern conditions, the late‐summer ammonium recycling signal outweighs that of wintertime decomposition on the annually integrated δ 15 N of sinking foraminifera. Plain Language Summary: Shells of foraminifera, single‐celled zooplankton, record information about their surroundings, making their fossils a useful tool for investigating past ocean conditions. Paleoceanographers have begun to use the ratio of heavy‐to‐light‐nitrogen isotopes in fossil foraminifer shells as a measure of past biological nitrate consumption in the Southern Ocean. But the isotopic link between living foraminifera and the nitrate consumed has only been tested in the subtropics, where surface nitrate is fully consumed by phytoplankton. In today's polar ocean, surface nitrate is only partly consumed and mostly during the productive spring/summer. Our goal was to investigate whether living foraminifera record the isotopic composition of nitrate consumed in Southern Ocean surface waters. We collected living foraminifera from the region south of Africa during winter and late summer, using a net towed by the ship. We found that the nitrogen in foraminifer shells and tissues most closely tracks the foraminifer's particulate nitrogen food. While nitrate and particulate nitrogen in surface waters are closely linked during spring/summer, the two can diverge because of nitrogen recycling in late summer and winter. Therefore, when interpreting foraminifer‐bound nitrogen isotope paleo‐records, we must consider the effects of these "off‐peak" seasons, as their influence may have been different at certain times in the past. Key Points: Foraminifer δ 15 N tracks bulk particulate organic N (rather than nitrate) δ 15 N in the Southern Ocean mixed layer on a seasonal basis Particulate N δ 15 N records early‐summer nitrate consumption, late‐summer ammonium recycling, and winter decomposition With today's seasonality, late summer is estimated to outweigh winter in its effect on the δ 15 N of foraminifera accumulated on the seabed